2020
DOI: 10.1186/s12870-020-02383-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and metabolome reveal redirection of flavonoids in a white testa peanut mutant

Abstract: Background: Coat color determines both appearance and nutrient quality of peanut. White seed coat in peanut can enhance the processing efficiency and quality of peanut oil. An integrative analysis of transcriptomes, metabolomes and histocytology was performed on wsc mutant and its wild type to investigate the regulatory mechanisms underlying color pigmentation.Result: Metabolomes revealed flavonoids were redirected in wsc, while multi-omics analyses of wsc mutant seeds and testae uncovered WSC influenced the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 73 publications
(81 reference statements)
1
25
1
Order By: Relevance
“…The above results show that in Ft, the particle flow does not stay at the CGAs stage but is synthesized downstream at a high rate. Similar results have also been reported in ginkgo and peanut species [ 46 , 47 ]. An organism is complex.…”
Section: Resultssupporting
confidence: 90%
“…The above results show that in Ft, the particle flow does not stay at the CGAs stage but is synthesized downstream at a high rate. Similar results have also been reported in ginkgo and peanut species [ 46 , 47 ]. An organism is complex.…”
Section: Resultssupporting
confidence: 90%
“…Among them, the expressions of DEGs encoding CHS , CHI , F3H , DFR and ANS were higher in PRL than in GL, which may result in higher anthocyanidin during the purple-red leaf stage. ANS genes play essential roles in anthocyanin biosynthesis, because they directly convert leucoanthocyanidins into colored anthocyanidins [ 30 ]. The lack of ANS and DFR activity results in the loss of pigmentation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genes in the pathway of anthocyanin metabolism are relatively conservative in different plants; for instance, for genes related to anthocyanin synthesis in C. humilis fruit peel, 23 transcripts encoding 11 enzymes were isolated. Three of the 11 were phenylalanine synthesis genes, including PAL, C4H and 4CL; six were flavonoid synthase genes, including CHS, CHI, F3H, F3'H, DFR, and ANS; one was a proanthocyanidin synthase gene, LAR; and one was an anthocyanin synthase gene, UFGT [36,38,52]. In our studies, the expression analysis of early genes showed that the expression of F3H in YF was higher than that in RF (Figure 8), suggesting that a large amount of dihydrokaempferol could be produced in YF, but this could not eventually outflow into anthocyanin synthase.…”
Section: Key Genes In the Anthocyanin Pathway Affect Coloration In Yellow And Red Fruit Peelmentioning
confidence: 99%
“…Additionally, metabolomics analysis could be regarded as a technical means of association analysis, together with other data, to analyze the function of genes involved in the metabolic pathway of interest and also provide powerful supporting information for gene mining [33][34][35]. In recent years, combined metabolome and transcriptome analyses in fruits have clarified the relationship between contents of various secondary metabolites and corresponding differentially expressed genes, broadening our horizons of plant color regulation [36][37][38]. Until now, C. humilis has been seen as a resistant ornamental plant.…”
Section: Introductionmentioning
confidence: 99%